1991
DOI: 10.1007/bf02537134
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary n−3 polyunsaturated fatty acids on HDL cholesterol in Chukot residentsvsmuscovites

Abstract: Native Chukot Peninsula residents, in contrast to Muscovites, consume a diet rich in n-3 polyunsaturated fatty acids. This dietary peculiarity is reflected in differences in plasma lipid and apolipoprotein contents. The Chukot residents have lower contents of total cholesterol, triglyceride, LDL (low density lipoprotein) cholesterol and apolipoprotein B, but higher HDL (high density lipoprotein) cholesterol levels than do Muscovites. The apolipoprotein A-I levels were identical in both groups. A higher HDL cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…CLA has long been accepted as having hypocholesterolemic effects [6]. Our observation of hypocholesterolemic activity of CLnA isomers has been confirmed by another study with some vegetable oils [8].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…CLA has long been accepted as having hypocholesterolemic effects [6]. Our observation of hypocholesterolemic activity of CLnA isomers has been confirmed by another study with some vegetable oils [8].…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies showed that linolenic acid derivatives, particularly gammalinolenic acid, were found to be even more potent in reducing blood cholesterol in humans and rats [7]. Those studies revealed that vegetable oil rich in polyunsaturated fatty acids are able to decrease the plasmatic levels of verylow-density lipoprotein (VLDL) and low-density lipoprotein cholesterol (LDL-C) and to increase the plasmatic level of high-density lipoprotein cholesterol (HDL-C) [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…28 This is consistent with the finding that diet-induced changes in the fatty acid composition of HDL 3 alter its ability to promote cholesterol efflux from cultured fibroblasts in vitro, 29 as well as in vivo. 30 This effect has been proposed to result from an inverse relationship between the fluidity and saturation of the HDL phospholipid acyl chains. 31 Effects of PLPC and DPPC containing rHDL on arterial cell morphology have been reported in a rabbit model in which acute vascular inflammation was induced by insertion of a nonocclusive peri-arterial collar.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone-binding globulin and cortisol-binding globulin were measured as described. 31 Serum lipids were assayed according to Gerasimova et al 32 Protein content was determined by the method of Lowry et al 33 with bovine serum albumin as the standard.…”
Section: Sds-page and Quantification Of Resultsmentioning
confidence: 99%